2016
DOI: 10.1177/105268461602600103
|View full text |Cite
|
Sign up to set email alerts
|

The Uncertainty of High Expectations

Abstract: Teacher turnover continues to be a chronic problem for low-income schools and is especially high in urban charter schools. New evidence shows that teachers' perceptions of school leadership and trust are two of the most powerful predictors of turnover. Using interviews with former No Excuses charter school (NECS) teachers, this study seeks to better explain the mechanisms influencing teacher turnover by analyzing teachers' perceptions of what principals do to influence relational trust and describing how this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…This makes teachers constantly faced with contextual decisions arising from students' needs and adversities in the classroom. Consistent with literature findings, high and often-implicit expectations of school administrators cause teacher anxiety and burnout (Torres, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…This makes teachers constantly faced with contextual decisions arising from students' needs and adversities in the classroom. Consistent with literature findings, high and often-implicit expectations of school administrators cause teacher anxiety and burnout (Torres, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Researchers have explored teacher experience and turnover in charters and CMOs from a range of perspectives, for example, working conditions and workload (Roch & Sai, 2017, 2018; Stuit & Smith, 2010; Torres, 2016a), disciplinary practices (Golann, 2021; Sondel et al, 2022; Torres, 2016b), autonomy and school-wide influence (Torres, 2014, 2019), and leadership (Boyd et al, 2011; Torres, 2016c). Surprisingly few researchers (Larkin et al, 2021; Watson, 2018; Yildiz, 2018) have explicitly used job embeddedness as a theoretical lens to study teacher retention and turnover despite its use in other fields for over two decades and despite its promise to serve as a predictor of retention (e.g., Shah et al, 2020; Tröster et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ndoye and colleagues (2010) conducted survey research in North Carolina and found that charter school teachers were more likely to report an intention to leave their jobs than their TPS counterparts. However, the literature suggests that supportive and effective school leadership is a predictor of teachers remaining in their jobs (Ndoye et al, 2010;Torres, 2016). In the private school sector, Lopes and Oliveira (2020) conducted a multilevel analysis of teacher and school determinants of job satisfaction and found that teaching in a private school was the strongest predictor.…”
Section: Teacher Job Satisfaction and Retentionmentioning
confidence: 99%